Methodological proposals for developing practices involving the interface between history and mathematics teaching (Research, Society and Development, 2021)
In the current scenario of Brazilian studies related to mathematical education, a highlight has been the articulation with the field of the history of mathematics. In this sense, it is understood that the history of mathematics provides resources that can be investigated through didactic and pedagogical issues with respect to mathematics teaching. Under an updated historiographic perspective, these studies search to understand the processes of elaboration, transmission, and transformation of mathematical ideas over time and incorporate them into methodological strategies that can contribute to the teaching process. With a view to unveiling this scenario, this study aims to discuss some methodologies used in research that involve the interface between history and the mathematics teaching. Thereunto, a systematic bibliographic search was carried out, searching for a debate and a reflection of reading articles and books related to the research object. Three methodological proposals related to studies involving the interface are perceived: documentary and historical, collaborative, and ethnographic research. These indications help future researchers to link the process of creating a praxis, action-reflection-action movement, to the updated historiographic perspective. Thus, aiming at future interventions in basic education, starting from the theories applied in the initial and continuing teachers training so that these professionals can transpose the concepts and methods in their teaching practice.